The Early Indicators of Functional Decrease in Mild Cognitive Impairment - Kubicki, Alexandre; Fautrelle, Lilian; Bourrelier, Julien; Rouaud, Olivier; Mourey, France (Frontiers in Aging Neuroscience, 2016)
OBJECTIVES: Motor deficiency is associated with cognitive frailty in patients with Mild Cognitive Impairments (MCI). In this study we aimed to test the integrity of the muscle synergy involved in an arm-pointing movement in MCI patients, non-impaired functionally. Thus, we were able to test the hypothesis that early motor indicators exist in this population at a preclinical level. METHODS: The electromyographic signals were collected for 11 muscles in 3 groups: Young Adults (YA), Aged Adults (AA), and MCI patients. The AA and MCI groups presented the same functional status. Each subject performed twenty arm-pointing movements from a standing position. RESULTS: The main differences were (1) delayed activation of the right Biceps Femoris and the right Erector Spinae at L3 in MCI patients and AA compared with YA groups ; (2) earlier activation of the left Obliquus internus in MCI compared with AA group and (3) concerning the left Erector spinae at L3, a delay for the AA compared with YA but an earlier activation for the MCI compared with both AA and YA. These temporal differences in muscle synergies were linked with executive functions of MCI patients. INTERPRETATION: The motor program changes highlighted in our patient (MCI) group suggest that discrete modifications of the motor command seem to exist even in the absence of functional impairment. Instead of showing an indication of delayed muscle activation in the MCI patients, our results highlight some early activation of several trunk muscles, probably used in a more cautious motor behavior.